90 days to success as a project manager - Sanghera, Paul. (Boston Course Technology Cengage Learning, 2009)
"90 Days to Success as a Project Manager" will help first-time project managers hit the ground running with any project during the critical first 90 days on the job. The book introduces readers to, and is organized around, the five keys to successful project management: initiating, planning, executing, monitoring and controlling, and closing the project. It covers all nine knowledge areas of project management: integration management, scope management, time management, cost management, quality management, human resource management, communication management, risk management, and procurement management. All this information could be very overwhelming for a beginner. However, this book makes the process interesting by explaining all concepts from scratch and presenting the "big picture" in a cohesive way. Whether your project duration is a few weeks, a few months, or a few years, and whether your project is in construction, biotechnology, or any other field, this guide will help you ensure that you manage the project effectively, efficiently, and successfully, and it will lay down the foundations for your success as a project manager in just three months!
Includes index.
Keywords: Project management